2020
DOI: 10.3390/ma13143145
|View full text |Cite
|
Sign up to set email alerts
|

Performance Characterization of Hot Mix Asphalt with High RAP Content and Basalt Fiber

Abstract: Incorporating reclaimed asphalt pavement (RAP) into asphalt mixtures achieves astonishingly environmental and economic benefits. However, there is hesitation to use higher RAP content due to the concern regarding the deterioration in pavement performance, especially the cracking resistance. Basalt fiber has been considered an effective additive to reinforce the performance of asphalt mixtures and, subsequently, the reinforcement effect is also expected for high-RAP content mixtures. Therefore, this study inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 44 publications
1
11
0
1
Order By: Relevance
“…This is because PVA fibers possess higher tensile strength than acrylic and polyester fibers. The same behavior was observed by several previous studies, in which the reinforced asphalt mixes have higher indirect tensile strength than the reference mixes [48][49][50][51]. Moisture susceptibility of the asphalt mixtures is considered as one of the main distress that influences the performance of the asphalt layer [52].…”
Section: Moisture Susceptibility Of the Reinforced Asphalt Mixturessupporting
confidence: 85%
“…This is because PVA fibers possess higher tensile strength than acrylic and polyester fibers. The same behavior was observed by several previous studies, in which the reinforced asphalt mixes have higher indirect tensile strength than the reference mixes [48][49][50][51]. Moisture susceptibility of the asphalt mixtures is considered as one of the main distress that influences the performance of the asphalt layer [52].…”
Section: Moisture Susceptibility Of the Reinforced Asphalt Mixturessupporting
confidence: 85%
“…The findings indicated that the low-temperature performance and fatigue resistance decrease with the increase in RAP content; meanwhile, the water damage resistance of bituminous mixture first increases (with 0-40% RAP), and then decreases (>40% RAP). Wu [11] indicated that the bituminous mixture containing 40% RAP had the greatest shear strength. The RAP increases the potential for low-temperature cracking in bituminous mixtures [12].…”
Section: Introductionmentioning
confidence: 99%
“…), asphalt properties, and mixture gradation. Many literatures were dedicated to the above factors [22][23][24][25][26], and the results indicated that some factors have to be strictly controlled to achieve the desirable mixture performance. Fortunately, the fiber properties, the proposed optimum fiber dosage selection for different mixture gradations, and the construction processes are specified in the newly issued guideline "Technical Guideline for Construction of Asphalt Pavement with Basalt Fiber" (T/CHTS 10016-2019) [27] and the provincial specification "Standard specification for construction of Asphalt Pavement with Basalt Fiber" (DB32/T 3710-2019) [28], which contribute to the standardized application of basalt fiber in the asphalt mixture and ensure the reinforcing effect to some extent.…”
Section: Introductionmentioning
confidence: 99%